2020
DOI: 10.1177/2325967120925486
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients With Patella Alta and/or Severe Trochlear Dysplasia Through the Presence of Patellar Apprehension in Higher Degrees of Flexion

Abstract: Background: Recurrent patellar instability is frequently treated surgically with reconstruction of the medial patellofemoral ligament (MPFL). Patients with significant patella alta, trochlear dysplasia, and/or an elevated tibial tubercle–trochlear groove (TT-TG) distance may benefit from a concurrent bony procedure such as tibial tubercle osteotomy or trochleoplasty. The indications to perform such procedures are traditionally based on imaging criteria but remain controversial. Patellar apprehension is common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Most notably, the results became positive at a mean knee flexion angle of 58 (20 -90 ). In addition, Colatruglio et al 8 reported that in 90% of patients with significant patella alta and in the majority of patients with high-grade trochlear dysplasia, patellar apprehension persisted beyond 60 of knee flexion; these findings are in line with the results obtained in this study and with biomechanical principles of the patellofemoral joint and might explain why isolated MPFL-R may not be sufficient in certain patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Most notably, the results became positive at a mean knee flexion angle of 58 (20 -90 ). In addition, Colatruglio et al 8 reported that in 90% of patients with significant patella alta and in the majority of patients with high-grade trochlear dysplasia, patellar apprehension persisted beyond 60 of knee flexion; these findings are in line with the results obtained in this study and with biomechanical principles of the patellofemoral joint and might explain why isolated MPFL-R may not be sufficient in certain patients.…”
Section: Discussionsupporting
confidence: 90%
“…First, the dynamic evaluation of the patellar apprehension test represents the patient-specific end of stable patellar tracking and the beginning of patellar stabilizer insufficiency. 8,48 Second, the J-sign evaluates patellar tracking during active knee joint motion, thereby reflecting overall patellar tracking or maltracking of an individual's anatomy, and it affects clinical outcome scores and graft laxity after MPFL-R. 20,29,44,45 Accordingly, 2 major forms of recurrent LPI might be proposed 2 : a mild form characterized by a positive patellar apprehension test result ranging from 0 to 40 (50 ) of knee joint flexion and an absent or low-grade J-sign (grade 1) and a complex form characterized by a positive patellar apprehension test result >40 of knee joint flexion and/or severe patellar maltracking (grade 2 or 3 J-sign).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, TT-TG measurements are often used to make surgical decisions about soft tissue stabilization and distal rearrangement [ 20 ]. This finding suggests that in patients with severe trochlear dysplasia, it seems the results obtained by TT-TG and TT-PCL are inconsistent, which will affect clinical judgment.…”
Section: Discussionmentioning
confidence: 99%
“…The Caton-Deschamps index was used to evaluate patella alta (Caton-Deschamps Index > 1,2) [ 20 ]. High-grade trochlear dysplasia was defined as Dejour types B, C, and D [ 21 ].…”
Section: Methodsmentioning
confidence: 99%